Lithuanian Language and Literature Program – a Medium for Deep Reading Education - Šileris, Arūnas (Knygotyra, 2022)
Researchers have been observing the deteriorating deep reading skills among pupils and highlighting the necessity to nurture them. Yet the concept of what ‘reading’ means (and ‘deep reading’ in particular) seems elusive. Deep reading may be interpreted in a number of ways. The difference in the notion of what constitutes deep reading calls for a closer investigation, with the view to delineating the two concepts.By drawing on the theoretical framework of Self-Determination Theory and Transportation theory, the article analyses two different approaches to deep reading in the light of a the recent draft curriculum of the Lithuanian language and literature for grades 5–12 of high school in Lithuania. The analysis has revealed that the current draft seems to be less focused on promoting the first type of deep reading associated with the deep emotional engagement (and hence higher levels of internal motivation) with literary texts. It is rather focused on the second type of deep reading that seeks to engage cognitive processes (and is more related to external motivation). Irrespective of the fact that the draft curriculum does make references to concepts associated with deep emotional involvement of readers (such as the pleasure of reading), this type of deep reading is not the main focus of the new curriculum.
Keywords: Deep reading; motivation to read; Lithuanian language and literature curriculum